Determinants of Claim Realization Death Benefit Program: Social Protection Analysis - Aquila Himawan; Eleonora Sofilda; Muhammad Zilal Hamzah (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2026)
The Death Benefit Program (JKM) is a key instrument within Indonesia’s employment-based social protection system, aimed at safeguarding workers’ households from the economic consequences of the death. This study examine to analyze the effects of labor market structure, macroeconomic conditions, human development, as well as program participation and financing on the number of JKM claims in Indonesia. This study employs a quantitative approach using panel data regression across Indonesian provinces (16) for the period 2018–2024. The results show that the proportion of formal workers, economic growth, IPM, and the number of JKM participants significantly affect the realization of JKM claims. In contrast, the total number of employed persons and the proportion of informal workers do not have a significant impact. These findings suggest that JLI claim realization is driven more by the quality of labor market integration into social insurance system and institutional capacity than by the size of the working population. This study contributes by positioning JKM claims as a policy outcome of risk based social protection and underscores the need to shift policy focus toward improving participation quality, promoting labor formalization, and strengthening governance to ensure sustainability and equity.